Pengaruh Minat Belajar Terhadap Kemampuan Penalaran Matematika Siswa Kelas VIII A SMP Bopkri 5 Yogyakarta - Selestina Moniz; Eva Nuryani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Mathematics learning needs to be designed so that it can accommodate various student characteristics (Rini, 2020). This is because until now there is no certainty about the meaning of mathematics because each expert has different knowledge and opinions. There are also those who state that mathematics is the science of numbers and space, symbolic language, numerical language, abstract and deductive science, logical thinking methods, science that studies the relationships between patterns, shapes and structures. Type of research used. In this research, quantitative methods were used. According to Sugiyono (2019) quantitative methods are research in the form of calculations and statistical analysis. This method aims to research a certain population, use research instruments in collecting data, analyzing data, with the aim of testing the hypothesis that has been determined. The first prerequisite test carried out is the normality test. This test was carried out to find out whether the research data was normally distributed. Normality test using the Shapiro Wilk formula with the help of the IBM SPSS Statistics application. The conclusion of the influence of interest in learning on the mathematical reasoning abilities of class VIII A students at SMP Bopkri 5 Yogyakarta, the author would like to convey suggestions to parties related to this research with the hope that it will be useful in the future. The results of the research analysis show that there is a significant influence between interest in learning on the mathematical reasoning abilities of class VIII A students at SMP Bopkri 5 Yogyakarta, amounting to 47.7%.